Penerapan teknik digital prototyping dalam perancangan dan pembuatan model produk berbasis generative design - Masy'ari Masy'ari; Edi Karyadi; Rusadi Rusadi (Universitas Muhammadiyah Metro, 2020)
Digital prototyping is an innovative design method. With digital product prototyping techniques that are designed with the concept of Generative Design and Topology Optimization, the designer able to visualize and simulate the product start from the design, stress analysis to the product manufacturing process. The aim of this research is to optimization the topology of the product model results of generative design, determine the strength of the model through Stress Analysis used topology optimization 50%, 60%, and 70% of the product model results of generative design and figure the results of the product 3D printing in made prototype models as a result of generative design. This research is conducted in 3 steps, that is the preparation of made models with computing Autodesk Inventor Professional 2020, the analysis with generative design, and the printed with 3D printing. This 3D printed product is made in 2 models. Model 1 with a material reduction of 70% topology optimization was better than 50% or 60% material lighting. Model 2, the maximum of 50% Von Mises Stress reduction is smaller than the 60% and 70% reduction.Keywords: Digital prototyping, generative design, topology optimization